A HUMAN RIGHTS REVIEW OF INTERFAITH MARRIAGE: BETWEEN THE UNIVERSALITY OF WESTERN HUMAN RIGHTS AND THE CONTEXT OF ISLAMIC SHARIA - Mudakir, Kharis; Nicko, Abed; Suprianto, Agus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Marriage is a sacred promise made by a man and his partner to become husband and wife. Basically, each religion has its own provisions regarding marriage. In fact, many interfaith marriages are found, especially this finding is found in Indonesia, where interfaith marriages are carried out so that this practice is a topic of discussion until now, and in practice, many Muslims still practice interfaith marriages. In this library research study, the aim is to examine how Western human rights and Islamic human rights view the practice of interfaith marriage in Indonesia. The results of this study show that from a Western human rights perspective, it can be concluded that the Compilation of Islamic Law as the legal basis for interfaith marriage in Indonesia is not in accordance with universal human rights principles that are anthropocentric in nature. Freedom of religion seems to be a threat to the Western view of human rights in Indonesia. Meanwhile, in Islamic human rights, the prohibition of interfaith marriage in the Compilation of Islamic Law is a natural and correct thing from an Islamic human rights perspective. Human rights and norms in society. In terms of freedom to form a family, religious values must be prioritized over anthropocentrism. This is what differentiates it from anthropocentric Western human rights. Islamic human rights not only recognize the rights of fellow human beings (lawful worship) but this right is based on the basic human obligation which is binding to serve Allah SWT (God bless you) which is theocentric in nature.